Language games in the novel "Piano Cafe" by Far had Jafri - Majid, Anwar Abbas (Al-Adab Journal, 2019)
Language games are among the combinations and concepts that share many similarities with linguistics, linguistics, literature, grammar, psychology, philosophy and sociology. Wittgenstein was the first to seriously play his linguistic games and functions. In his view, he emphasized the philosophical and linguistic aspects and focused on the functioning of language in people’s lives. Wittgenstein considered language use by people to function as a benchmark of language. Language games in literature are assigned to the use of vocabulary, phrases and sentences in the language applications of individuals. These include repetitions, linguistic constructs, grammatical functions, use of vocabularies, interactive applications and the use of broken languages, linguistic imaging, the presentation and attribution of attributes and attributes, types of aggregation, the construction of derivative vocabulary, and the use of short and long sentences. In this study, the author will examine the language games in the novels of the piano’s cafe from the perspective of literature and components discussed.